Using the International Classification of Functioning, Disability and Health (ICF) to Describe Children Referred to Special Care or Paediatric Dental Services. - Faulks D; Norderyd J; Molina GF; MacGiolla C; Scagnet G; Eschevins C; Hennequin M (2019)
Children in dentistry are traditionally described in terms of medical diagnosis and prevalence of oral disease. This approach gives little information regarding a child?s capacity to maintain oral health or regarding the social determinants of oral health. The biopsychosocial approach, embodied in the International Classification of Functioning, Disability and Health - Child and Youth version (ICF-CY) (WHO), provides a wider picture of a child?s real-life experience, but practical tools for the application of this model are lacking. This article describes the preliminary empirical study necessary for development of such a tool - an ICF-CY Core Set for Oral Health. An ICF-CY questionnaire was used to identify the medical, functional, social and environmental context of 218 children and adolescents referred to special care or paediatric dental services in France, Sweden, Argentina and Ireland (mean age 8 years 63.6yrs). International Classification of Disease (ICD-10) diagnoses included disorders of the nervous system (26.1%), Down syndrome (22.0%), mental retardation (17.0%), autistic disorders (16.1%), and dental anxiety alone (11.0%). The most frequently impaired items in the ICF Body functions domain were ?Intellectual functions?, ?High-level cognitive functions?, and ?Attention functions?. In the Activities and Participation domain, participation restriction was frequently reported for 25 items including ?Handling stress?, ?Caring for body parts?, ?Looking after one?s health? and ?Speaking?. In the Environment domain, facilitating items included ?Support of friends?, ?Attitude of friends? and ?Support of immediate family?. One item was reported as an environmental barrier ? ?Societal attitudes?. The ICFCY can be used to highlight common profiles of functioning, activities, participation and environment shared by children in relation to oral health, despite widely differing medical, social and geographical contexts. The results of this empirical study might be used to develop an ICF-CY Core Set for Oral Health - a holistic but practical tool for clinical and epidemiological use.